2021
DOI: 10.7759/cureus.16016
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Patient Satisfaction With the Trend of Virtual Clinics During the COVID-19 Pandemic

Abstract: BackgroundThe consequences of the coronavirus 2019 (COVID-19) pandemic on healthcare systems worldwide are undeniably disrupting regularly provided care for non-COVID-19 patients. Since the start of the pandemic, medical services in Saudi Arabia have adapted to the situation by providing medical care through virtual clinics. This article aims to evaluate patient satisfaction with virtual clinics during the COVID-19 pandemic. Material and methodsA cross-sectional study was conducted among patients who had exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…These results show that both treatment modalities are effective with respect to the HRQoL of patients with dermatological afflictions. Some studies advocate the combination of TD and F-F/D to obtain benefits from both [ 44 ]. For this, TD must be part of the toolbox available to the health professional, considering the numerous advantages for the health system from a social and economic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…These results show that both treatment modalities are effective with respect to the HRQoL of patients with dermatological afflictions. Some studies advocate the combination of TD and F-F/D to obtain benefits from both [ 44 ]. For this, TD must be part of the toolbox available to the health professional, considering the numerous advantages for the health system from a social and economic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that telehealth is safe and effective for postoperative care, further indicating its potential as an ideal tool for pediatric obesity management [40]. Formal surveys of 123 patients who utilized virtual clinics during the COVID-19 pandemic revealed a high level of satisfaction, particularly within the dermatology and psychiatry clinic setting [41]. This technology can provide a realistic, low-cost, and easily accessible option for pediatric patients to engage with a weight management team, improving access to care [42].…”
Section: Telehealth As a Useful Tool In Addressing Pediatric Obesitymentioning
confidence: 99%
“…McGrail et al indicated that 93% stated that the virtual visit was of high quality and 91% indicated that the virtual visit was useful in resolving their health issues, indicating high patient satisfaction [ 6 ]. Additionally, others indicated that, during the pandemic, the quality of virtual clinic service was comparable to actual office visits with the additional benefit of fast access to care [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%